If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(y-3)=-7y-18
We move all terms to the left:
-4(y-3)-(-7y-18)=0
We multiply parentheses
-4y-(-7y-18)+12=0
We get rid of parentheses
-4y+7y+18+12=0
We add all the numbers together, and all the variables
3y+30=0
We move all terms containing y to the left, all other terms to the right
3y=-30
y=-30/3
y=-10
| 2x+3-4×-28=-1-20x+60 | | -8w+27=5(w+8) | | 6x-5/6=1/6 | | 2/3l-1=37 | | 50x^2-x=0 | | 15x=720 | | -2(1/3)+y=-2 | | n+3/2-n-2/5=n+1/10-1 | | 1/5x+1/4=-3(4/5x+3) | | 4(x-6)=5x+11 | | x/2+3/4=5/4 | | 4/7-7/7x=3/7 | | -4/5+y=-2 | | -n+-n−20n−-20n=6 | | r*r-7r=0 | | 2x-3/4=13/4 | | 960(1+r)^2=1123.60 | | x=24/5 | | 4=4x^2+3x | | 3(3x+4)=-5(x-8) | | 6/5x-3/2=-2/3 | | 14j−16j−-6j−-4j−-5j=13 | | 3q-2q=17 | | 16x+18-10x+14=80 | | 6=8.3^x | | x-4/5=61/2 | | 12/24=4/x | | 60s+2=8 | | 3m+2=9m | | 12c-11c=15 | | 92=4(j-3)+8 | | 10w-9w=12 |